Gut-skin axis: unravelling the connection between the gut microbiome and psoriasis - Thye, Angel Yun-Kuan (2023)
Evidence has shown that gut microbiome plays a role in modulating the development of diseases beyond the gastrointestinal tract, including skin disorders such as psoriasis. The gut-skin axis refers to the bidirectional relationship between the gut microbiome and skin health. This is regulated through several mechanisms such as inflammatory mediators and the immune system. Dysregulation of microbiota has been seen in numerous inflammatory skin conditions such as atopic dermatitis, rosacea, and psoriasis. Understanding how gut microbiome are involved in regulating skin health may lead to development of novel therapies for these skin disorders through microbiome modulation, in particularly psoriasis. In this review, we will compare the microbiota between psoriasis patients and healthy control, explain the concept of gut-skin axis and the effects of gut dysbiosis on skin physiology. We will also review the current evidence on modulating gut microbiome using probiotics in psoriasis.